2021
DOI: 10.18240/ijo.2021.05.15
|View full text |Cite
|
Sign up to set email alerts
|

Optical and visual quality comparison of implantable collamer lens and femtosecond laser assisted laser in situ keratomileusis for high myopia correction

Abstract: AIM: To compare clinical outcomes and refractive stability of implantable collamer lens (ICL) implantation and femtosecond laser assisted laser in situ keratomileusis (FS-LASIK) for high myopia correction. METHODS: The Optical Quality Analysis System (OQAS) was used to evaluate clinical outcomes objectively after operation for high myopia correction. We compared the two procedures in terms of 1-year changes in uncorrected distance visual acuity (UDVA), corrected distance visual acuity (CDVA), safety index, eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 23 publications
1
23
0
Order By: Relevance
“…22 articles were further excluded due to the following reasons: study in Czech (n=1), studies where only ICL implantation was performed (n=2), studies where subjects were children (n=2), studies recruited subjects of low or moderate myopia, or emmetropia (n=16), studies of iris-fixated Artiflex lens (n=1). Finally, 5 studies [ 13 , 16 , 18 , 20 , 21 ](involving 555 eyes) were included in this meta-analysis.
Fig.
…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…22 articles were further excluded due to the following reasons: study in Czech (n=1), studies where only ICL implantation was performed (n=2), studies where subjects were children (n=2), studies recruited subjects of low or moderate myopia, or emmetropia (n=16), studies of iris-fixated Artiflex lens (n=1). Finally, 5 studies [ 13 , 16 , 18 , 20 , 21 ](involving 555 eyes) were included in this meta-analysis.
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…Three studies [ 16 , 18 , 20 ] assessed change in Snellen lines of CDVA (Fig. 3 ), the heterogeneity across three studies was small (I 2 =50%), so a fixed-effects model was applied.…”
Section: Resultsmentioning
confidence: 99%
“…16,17,24 Mean postoperative UDVA values were in favor after T-ICL over LASIK in 3 articles, but only Jiang et al showed significance. 20,25,26 Several studies reported a significantly higher predictability within ±0.5 D and ±1.0 D in ICL over LASIK for moderate to high myopia and within ±1.0 D for high myopia. 16,17,21,24 Jiang et al reported a remarkable difference of predictability within ±0.5 D in favor of ICL (ICL 98% vs FS-LASIK 69%, significance unknown).…”
Section: Discussionmentioning
confidence: 99%
“…Alternative optical quality parameters are used to quantify visual quality after presbyopia-correcting IOLs implantation in eyes that have had refractive surgery, including the modulation transfer function (MTF) cutoff frequency, the objective scatter index (OSI) and the strehl ratio (SR). MTF is obtained by Fourier transform from the point spread function (PSF) and MTF cutoff is used to express visual quality, referring to the frequency at which the MTF reaches 1% contrast ( 39 ). OSI is defined as the amount of the light outside the double-pass retinal intensity PSF image in the peripheral zone vs. that on the central zone ( 40 ).…”
Section: Discussionmentioning
confidence: 99%